Indonesian Government's Strategy In Dealing With The Development Of Biological Threat In Indonesia By Utilizing The Role Of Intelligence - Alif Hanugrah Insan Nanda Pratama Surakusumah; Dimas Raka Kurniawan Putra (Soshum: Jurnal Sosial dan Humaniora, 2025)
The Indonesian government is facing the threat of developing biological threats that exist in Indonesia by utilizing the role of intelligence. Biological threats can develop into potential biological weapons because the impact of biological weapons threats is mass and can affect various aspects of a nation's life, both from economic, socio-cultural and defense and security aspects. The aim of this research is to evaluate the Indonesia's strategy in facing threats that exists in Indonesia, especially biological threats, by using intelligence. Sishankamrata is a defense system that consists of three components: biological accidents, biocrime, natural events, lab accidents, inodemic hoaxes, gray area incidents, and public health emergency of international concern (PHEIC). It is hoped that this research can be theoretically useful, namely that it can contribute to knowledge in the fields of defense and intelligence to face threats that existed in Indonesia. This research is aimed at identifying biological agents that have the potential to become bioweapons and their distribution mechanisms to prepare effective countermeasures from the resistance system national health.